(3OQGSI GdLOhi hfXGe (BB-O-Ts - (3ej(B, (3WhHGQs ((3GdbGgQI(B:s (3OGQ GdaGQhb GdGSJKeGQGJ GdKbGajI(B,s, 2006)
(3JYQja fXGe (BB.O.T (3hGge GdLhGfH GdGjLGHjI hGdSdHjI hGdeNGWQ GdeMjWI Hg, GdefXeGJ GdYdejI GdOhdjI hJLGQH HYV GdOhd GdeWHbI dfXGe (BB.O.T (3GSJNOGe GdeYdheGJ GdeMGSHjI aj WQb Jbjje eTQhYGJ GdHjFI GdCSGSjI GdeWHbI HfXGe (BB.O.Ts
Keywords: (3GdeTQhYGJ(B-(3JUajIs; (3OQGSI GdLOhis